Enhancing Africa's stroke workforce to address the stroke burden: a proposal from the African's stroke organization's educational and training committee - Paul Bolaji; Ebenezer Ad Adams; Rufus Akinyemi; Mayowa Owolabi; Foad Abd-Allah (Frontiers in Stroke)
Stroke is the second leading cause of death and disability in Africa, disproportionately affecting individuals in their most productive years and placing an immense socio-economic burden on families and healthcare systems. Despite the growing stroke burden, Africa faces a severe shortage of trained stroke specialists, with only three neurologists per 10 million people compared to up to 900 per 10 million in high-income countries. This gap has led to inadequate acute management, limited rehabilitation services, and poor long-term outcomes. To address this crisis, the African Stroke Organization (ASO) established an Education and Training Committee focused on developing a structured stroke education framework. This proposal outlines ASO's strategic initiatives to build stroke care capacity through research, professional training, service development, and advocacy. By implementing a comprehensive stroke education program-including online courses, hands-on workshops, conference-based training, and a future summer school, ASO aims to train 5,000 by 2030. Through this initiative, ASO seeks to empower African healthcare professionals, reduce disparities in stroke care, and ultimately improve stroke outcomes across the continent. This proposal presents the rationale, objectives, and implementation strategies for the ASO Stroke Education Program and calls for international collaboration to support this critical effort.